Bullet embolus to the right ventricle following shotgun wound to the leg - Hussein, Nabil (BMJ Case Rep, 2012)
Bullet embolism to the heart is a rare complication of gunshot trauma to the body and if not identified can have a severe impact on a patient's morbidity and mortality. This paper presents the case of a patient who sustained a shotgun wound to the leg 10 years prior to presenting with shortness of breath and localised chest pain. Routine chest radiograph for possible chest infection was reported normal apart from a small metallic artefact overlying the left side of the heart, which had the same appearance as the pellets from the gunshot wound in the leg. Following referral to our cardiothoracic surgeons, further investigations confirmed the presence of a pellet within the patient's right ventricle, which had embolised from the original injury site. The case was discussed globally to decide on the best management plan. To date, the patient has been successfully managed conservatively, with regular follow-up.